Necrotizing fascitis of male genitalia: A series of fifty-four consecutive patients - M EL Khafifi; K Mohammed; W.E.Y Alaorfi; A Osman (Libyan International Medical University Journal)
Background: Fournier's gangrene (FG) is a fulminant aggressive necrotizing fascitis affecting the external genitalia, perineum and anterior abdominal wall with significant mortality rate. The aim of the present study was to describe the associated risk factors, presentation, diagnosis, management and outcome of this condition in Benghazi, Libya. PATIENTS & METHODS: Over a period of twenty years (from January 1997 to October 2016) a series of 54 consecutive patients who were admitted to Urology Department, Hawari Center for Urology and Otolaryngology, Benghazi-Libya were evaluated retrospectively to assess the risk factors, etiology, management and outcome of this fatal disease. Results: It was found that 37 (68.5%) of patients were diabetics and 24 patients (44.4%) had perianal abscess as predisposing factor. Mortality rate was 14.8% (8 patients). All cases diagnosed on clinical basis. The patients operated promptly by extensive debridement. Reconstructive surgery done by flap or graft in plastic department to close the skin defect in most of our patients (41 patients, 75.9%). Conclusion: The main co-morbidity and predisposing factors of FG are diabetes mellitus and perianal abscess respectively. Prompt aggressive debridement is the only management to save the patient's life.